Analysis of the Village Head's Leadership Style in Cidokom Gunung Sindur Village, Bogor District - Gunartin Gunartin (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Profit is not the main goal of the cooperative business, but the business that is managed by the cooperative must obtain the remaining business results that are feasible so that the cooperative can maintain its survival and improve the ability of its business. This study aims to determine the effect of the number of members, own capital, external capital, business valves, and assets owned to the remaining results of business (Indonesian terms: Sisa Hasil Usaha/SHU) savings and loan cooperatives in Subang district. The sampling technique used was purposive sampling so as many as 14 cooperatives were selected. Data analysis used in this study is classical assumption analysis and then panel data analysis is carried out, determination of test coefficients (R2), F statistical tests, t statistical tests. Based on the results of research that has been carried out simultaneously known all independent variables significantly influence the residual business results. However, the partial test shows that only the variables of business capital, business volume, and assets owned by cooperatives have an effect on the residual results of operations, while the variable number of members and external capital has no effect on the residual results of operations.